Analysis of Science Teachers' Content Knowledge on the Concept of Global Warming - Meili Yanti; Haryanti Putri Rizal (South Sulawesi Education Development (SSED), 2025)
The ability of teachers to interpret the curriculum is essential in the preparation stage of teaching. This ability includes how teachers sequentially organize content from simple to more complex material. Teachers are also expected to master the subject matter, meaning they have broad and deep understanding of the material. Therefore, the aim of the research is to explore teachers' understanding of the material taught. This research was conducted using a descriptive method by applying an instrument for understanding the concept of global warming. The participants in this study were 19 Science teachers who are members of the Science Teachers Working Group (MGMP) in Majene Regency, West Sulawesi. The results showed that, in general, Science teachers have fairly good CK, evidenced by the percentage of teachers with moderate and high CK being 55% and 15%, respectively. Teachers understand the topic being discussed. However, not in depth or not mastered well. This is evidenced by the lack of depth of teachers' answers related to a problem, in other words, teachers cannot elaborate on the answers with things that can be accepted by students.